2008
DOI: 10.1002/path.2314
|View full text |Cite
|
Sign up to set email alerts
|

Expression of pentraxin 3 (PTX3) in human atherosclerotic lesions

Abstract: Pentraxin 3 (PTX3) and C-reactive protein (CRP) are members of the pentraxin superfamily. PTX3 expression is induced in response to inflammatory signals, and is produced at sites of inflammation by several types of cell, primarily monocytes/macrophages, dendritic cells (DCs), endothelial cells, smooth muscle cells (SMCs), and fibroblasts, but is not produced by hepatocytes, which are a major source of CRP. The aim of our study was to investigate the expression pattern of PTX3 in human atherosclerotic lesions u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
158
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(165 citation statements)
references
References 25 publications
5
158
1
1
Order By: Relevance
“…The relative increase in PTX3 at 24 h after coronary stenting was the most powerful predictor of late lumen loss. 19 As PTX3 was significantly higher in the unstable angina pectoris group compared with the control group, 20 and because macrophages expressed PTX3 in advanced atherosclerotic lesions, and PTX3-positive neutrophils infiltrated into coronary atherosclerotic plaques removed from patients with acute MI, 7 ARB might have a critical role in antiatherogenesis and prevent cardiac events through suppression of PTX3. There were no significant changes in PTX3 or hs-CRP between the BMS and DES groups in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relative increase in PTX3 at 24 h after coronary stenting was the most powerful predictor of late lumen loss. 19 As PTX3 was significantly higher in the unstable angina pectoris group compared with the control group, 20 and because macrophages expressed PTX3 in advanced atherosclerotic lesions, and PTX3-positive neutrophils infiltrated into coronary atherosclerotic plaques removed from patients with acute MI, 7 ARB might have a critical role in antiatherogenesis and prevent cardiac events through suppression of PTX3. There were no significant changes in PTX3 or hs-CRP between the BMS and DES groups in this study.…”
Section: Discussionmentioning
confidence: 99%
“…PTX3 is expressed in advanced atherosclerotic lesions. 7 Treatment with ARBs leads to a decrease in inflammation and adhesion molecules, such as CRP, 8 intercellular adhesion molecule-1, chemokines, E-selectin and monocyte chemotactic protein (MCP)-1. 9,10 In addition, monocyte and endothelial cell activation markers were significantly decreased in patients with type 2 diabetes after treatment with valsartan.…”
Section: Introductionmentioning
confidence: 99%
“…10) PTX3 is produced at sites of infl ammation, and it is intimately linked to endothelial dysfunction. 23) Gustin, et al 24) demonstrated that lysophosphatidic acid, a major bioactive lipid component of oxidized lowdensity lipoproteins, induces both PTX3 expression and mRNA in endothelial cells in vitro. Circulating endothelial progenitor cells levels mobilized by endothelial dysfunction are associated with PTX3 levels in patients with peripheral artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies implicate both molecules in the worsening of endothelial function: PTX3 has been detected in atherosclerotic lesions and implicated on neointimal thickening (41,42). However, the recent observation that double knockout mice lacking ApoE and PTX3 displayed an increment in aortic lesion size and a higher inflammatory response compared with ApoE knockout mice expressing PTX3 (43) has lead to the hypothesis that PTX3 may be a failed compensatory mechanism to endothelial damage.…”
Section: Discussionmentioning
confidence: 99%